The institution of work-dorms in Turkey - Uğur, Hande Gökşin. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
The purpose of this thesis is to evaluate the contemporary situation of the prison-labor in Turkey through adopting a political economic perspective. The significance and the new role that prison-labor gained regarding the transformation occurred in the Turkish penal system in the 21st century constitutes the main point of research. In this regard, the Institution of Work-dorms that is established in 1997 is analyzed throughout the thesis along with the historical aspects of the penal regime in Turkey. Through the analysis of legislation, archival material, official documents, and reports, I study the manifestations of neoliberal regulation, especially the forms of new public management, in the penal field by means of the advancement of the prison-labor. As I explore the link between the work and punishment, I argue that the neoliberal implementations of the rehabilitative model in the penal regime after 2004 cause the subordination of a social aim into an economic aim, while the involvement of the private sector within the system underscores the aspects of new public management. Since the studies conducted on the Turkish penal system mostly involved the issue of political prisoners, the aim of this study is to contribute to the social sciences literature through providing a political economic analysis of the state-punishment relations, while shedding a light on the aspects of the contemporary political economy of Turkey through the analysis of the penal field.
Keywords: Convict labor -- Turkey.; Prisons -- Turkey -- History.